التنبؤ عن التخريج الآمن من قسم الإسعاف في التهاب القصيبات الشعرية - حكيم مأمون (Latakia University Journal -Medical Sciences Series, 2019)
هدف البحث وأهميته: يعتبر التهاب القصيبات الشعرية السبب الرئيس للاستشفاء عند الرضع. كان هدف دراستنا معرفة العوامل المترافقة مع التخريج الآمن من قسم الإسعاف إلى المنزل. طرائق البحث ومواده: دراسة مستقبلية 2009-2010 في قسم الإسعاف في مستشفى الأسد الجامعي في اللاذقية للأطفال المراجعين بتشخيص التهاب قصيبات شعرية وعمرهم دون السنتين. النتائج: شملت الدراسة 80 طفلاً، 57 (71%) تخرجوا للمنزل من قسم الإسعاف و23 (29%) قبلوا في المستشفى. أظهرت الدراسة العوامل المنبئة عن التخريج الآمن إلى المنزل, وهي: عمر أكبر من شهرين، الولادة بالطريق الطبيعي، عدم وجود أمراض مرافقة، غياب أو سحب ضلعي بسيط، إشباع الأكسجين البدائي ≥ 94%، بقاء القدرة على الرضاعة كافية، معدل التنفس في الدقيقة أقرب للطبيعي وصورة الصدر الطبيعية. الخلاصة: استطعنا من خلال الدراسة معرفة عدد من العوامل المترافقة مع التخريج الآمن للمنزل من قسم الإسعاف في التهاب القصيبات الشعرية، مما يساعد الطبيب الممارس في تقييم الطفل ويقلل من الاستشفاء غير الضروري. Objective: Bronchiolitis is the leading cause of hospitalization for infants. Our objective has been to identify factors associated with safe discharge to home from the emergency department. Methods: We conduct a prospective study during bronchiolitis season 2009-2010 in Emergency Department of AL-ASSAD University Hospital in Lattakia, for infants aging <2 years, presenting with bronchiolitis. Results: of 80 enrolled Childs 57 (71%) were discharged home from the Emergency Department and 23 (29%) were admitted to the hospital. The following factors predicted safe discharge to home: age >2 months, vaginal delivery, absence of concomitant medical disorder, no/mild retractions, initial oxygen saturation of ≥94%, adequate oral intake, respiratory rate near to normal for age and normal chest x-ray. Conclusion: This study of children presenting to the Emergency Department with bronchiolitis identified several factors associated with safe discharge to home. It will assist clinician evaluating children with bronchiolitis and reduce unnecessary hospitalizations.